In the network of healthcare actors: A study of family-centred care for children with complex needs Understanding and improving the respiratory care for children with cerebral palsy and multiple disabilities - Arnholm, Karin (My University, 2018)
Problem: Families to children with complex care needs face challenges in the Swedish healthcare system. Increasing differentiation and specializations without integration and coordination of healthcare actors has resulted in fragmentations and sub-optimizations within the system. The system has significant issues to align goals between actors and to establish clear roles and responsibilities between them. Simultaneously, the system suffers from poor leadership and lack of cross-functional collaboration, which result in old and inefficient processes, short-term solutions and reactive healthcare. Today healthcare actors do not know what other actors are taking or not taking responsibility for. Professionals are hindered to achieve holistic care, which increases the risk of working with contradictory treatments. The consequences for families to children with complex care needs are not only lack of involvement and family-centred care. The challenges increase the risk of diseases and reduce the children’s chances of receiving proactive and coordinated respiratory care. In worst case, these children die an early death. Method: Observations and interviews with about 20 healthcare actors, such as professionals at habilitations and hospitals, and interviews with four families to children with complex care needs, were held. The interviews and observations took place at the hospitals, in the homes of the families and over phone. The questions emphasized the families’ well-being, how healthcare professionals managed families with complex care needs and how they managed respiratory issues. The answers were then compared, analysed and summarized into different focus areas. Result: The study resulted in an overview of how families to children with complex care needs were managed and prioritized by different healthcare actors in Region Västra Götaland. Significant differences were identified, where most healthcare professionals lacked adequate prerequisites to create family-centred care in an efficient and proactive way. Common challenges for the professionals were lack of clear guidelines and responsibilities, inexistent or scarce collaboration with other key actors and lack of competence. The study identified inefficient processes, where professionals either performed contradictory treatment or wasted time on non-value adding activities. Instead of working as a collaborative network, with the aim to create holistic care greater than the sum of each actors’ contribution, the actors focused on their own organizational benefit. Consequences were not only conflicts and sub-optimizations, but also reactive and inefficient management of respiratory issues. Those professionals who worked in cross-functional teams and focused on adequate and proactive care were identified as most successful. Availability, involvement and flexibility were key factors when collaborating with families to children with complex care needs. The interviewed families were satisfied with having a competent and experienced respiratory team at their local hospital, who they could contact whenever they needed. The families emphasized the importance of coordinated and family-centred care, with the opportunity to co-create value. Followed early and often by a respiratory team resulted in increased well-being of and reduced hospitalizations. Conclusion: The study identified a Swedish healthcare system with poor management and individualistic perspectives, with actors who focused on their own organization rather than on their patients. A healthcare system full of fragmentations and lack of collaboration will never create anything else than sub-optimizations and low quality of care. While vulnerable families continue to struggle to avoid losing their children in early deaths, the healthcare system remain chaos without any sign of coordinated and synergized care. Even though the respiratory system is vital to every human being, few healthcare actors seem to focus on adequate and proactive care. According to this study, patients in need of coordinated care still are too complex for the system to manage and Sweden’s vision of ensuring everyone efficient and equal access to healthcare services has never felt so far away.
Keywords: Industriell organisation, administration och ekonomi; Industrial organisation, administration and economics